Role of Survey Department In Disaster Management In Nepal - Shrestha, Suresh Man (Journal on Geoinformatics, Nepal, 2012)
The Himalayan Range is a young mountain system of the world and about 83% of the total area of Nepal is covered by high hills and mountains. Major river systems of Nepal originate from the glaciers and are perennial in nature. According to the preliminary results of the Census 2011, more than 50% of total population live in Terai and are vulnerable to flood. Since Nepal falls under the seismically active zone earthquake has been one of the major disasters experienced in the country. Fire, Glacier Lake Outburst Flood, lightening, hail storm are some other natural disaster claiming lives of Nepalese people. It is not possible to stop disasters, but the consolidated effort of different organization may make us better prepared to overcome the negative impacts of such disasters. This article tries to explore the role of Survey Department in this context.